On The Use of Euphemism As A Means of Indirect Communication in Society (Web of Teachers: Inderscience Research, 2023)
In this article, the author examines the concept of euphemism and euphemistic replacement. The author addresses the issues of the connection between linguistic taboo and euphemism and determines the modern functions of euphemistic substitutions, which include veiling and masking the essence of the signified, ennobling speech. Euphemisms in this context serve for successful and conflict-free communication.